On Soft LC-Spaces and Weak Forms of Soft LC-Spaces - Mahmood, Sabiha I. (Iraqi Journal of Science, 2018)
The main purpose of this article is to study the soft LC-spaces as soft spaces in which every soft Lindelöf subset of is soft closed. Also, we study the weak forms of soft LC-spaces and we discussed their relationships with soft LC-spaces as well as among themselves.